(3CSHGH GdfRhds - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj (B468(3g`s ((3GdbGgQIs)
(3ChdgG (B:s
(3aj ChdgG eWGdYI d`(B: (3CHh Gdjef YHO Gddgs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs